Visualizing Nonradiative Mobile Defects in Organic–Inorganic Perovskite Materials. Issue 7 (8th April 2019) - Hentz, Olivia; Singh, Akshay; Zhao, Zhibo; Gradečak, Silvija
Abstract: Organic–inorganic perovskite materials have mobile charged point defects that migrate in response to voltage biasing and illumination, causing device performance variation over time. Improvements in device stability and reliability require methods to visualize point defect migration, estimate ionic mobilities, and identify factors influencing their migration. In this work, a versatile method is demonstrated to track nonradiative point defect migration in situ. Photoluminescence mapping of laterally biased perovskite films is used to track continuous changes in nonradiative recombination as charge‐trapping defects migrate between the device electrodes. A Monte Carlo framework of defect drift and diffusion is developed that is consistent with experimental photoluminescence observations, which combined enables point defect mobility estimation in methylammonium lead iodide films. Furthermore, measurements performed on materials with varied grain sizes demonstrate that point defect mobility is 1500× faster at grain boundaries compared to bulk. These findings imply that grain morphology can be used to tune point defect mobility such that large‐grained or single‐crystal materials inhibit point defect migration. The methods used in this work can be applied to visualize and quantify the migration of charge‐trapping point defects in a wide range of state‐of‐the‐art perovskite materials targeted toward reduced ionic mobilities and superior device stability. Abstract : Photoluminescence mapping of lateral organic–inorganic perovskite devices allows for direct tracking of mobile defects. By tracking the evolution of photo‐luminescence intensity, increase across laterally biased organic–inorganic perovskite films, the mobility, and charge of nonradiative point defects are uncovered. These methods are then used to demonstrate the degree to which grain boundaries facilitate point defect migration.